Synthesis and comparative biological analysis of mixed NHC/L platinum (II) complexes: anticancer and antimicrobial properties (Vol 1366, 146127, 2026) - Aslan, Sumeyye; Bugday, Nesrin; Boulebd, Houssem; Yuce, Hande; Turkmen, Nese Basak; Ozek, Dilan Askin; Unuvar, Songul (Elsevier, 2026)
[Abstract Not Available]
Keywords: [Keyword Not Available]